Positive impact of nutrition in the prevention of peripheral vascular disease and severe acute respiratory syndrome coronavirus 2: review - Karim, Zubair A.; Reese, Rebecca A.; Smith, Adrianne N.; Blackadar, Madeline E.; Arora, Vishal; Moore, Nicole M.; Johnson, Emily A. (Frontiers in Nutrition, 2024)
Recent research has shown that there is a link between the trend of cardiovascular disease (CVD), chronic symptoms of SARS-CoV-2 (COVID-19), and medical nutrition therapy. Making positive changes to an individual’s lifestyle can help to reduce the symptoms that follow exposure to CVD and COVID-19. Sustainable nutrition and lifestyle changes can positively impact an individual’s health. Studies have considered the risk factors associated with the disease, medical history, the link between nutrition and peripheral vascular disease (PVD), symptom management, and the interrelationship between nutrition, COVID-19, and PVD. One study has demonstrated that Western Dietary intake can boost the innate immune system while suppressing humoral response, causing chronic inflammation and poor host defense against viruses. However, further investigation is needed to confirm. Patients with PVD and COVID-19 have experienced a reduction in side effects when prescribed a regimen of medical nutrition therapy, heart-healthy diets, and adequate physical activity before and after symptoms of both diseases appear. This approach has proven to be a protective factor during the combination of both illnesses. Our findings indicate that balanced diets and lifestyles are essential in supporting an optimal immune system that can reduce the risk of virus load in individuals at risk of infection and symptoms from COVID-19 and PVD.